An Investigation of Surface States Energy Distribution and Band Edge Shifts in Solar Cells Based on TiO2 Submicrospheres and Nanoparticles. (1st April 2017) - Zheng, Jia-Wei; Mo, Li-E.; Chen, Wang-Chao; Jiang, Ling; Ding, You-Cai; Ding, Yong; Li, Zhao-Qian; Hu, Lin-Hua; Dai, Song-Yuan
Graphical abstract: Highlights: TiO2 submicrospheres are synthesized by a two-step method. The surface states of TiO2 submicrosphere and particle are studied. The band edge shift of the two films is investigated. The effect of surface states on the electron transport is characterized. Abstract: TiO2 submicrospheres were often used as photoanodes in dye-sensitized solar cells (DSSCs) due to the high internal surface area and great scattering properties. However, surface states in TiO2 submicrospheres limit the electron transport process. In this paper, an investigation of surface states in TiO2 submicrospheres and traditional TiO2 nanoparticles was conducted by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The chemical capacitance, electron transport resistance and recombination resistance were interpreted in a consistent framework. The electron transport and recombination behavior were also studied by open-circuit voltage decay measurements (OCVD) and intensity-modulated photocurrent/photovoltage spectroscopy (IMPS/IMVS). The results show that the TiO2 submicrospheres based films possess a larger number of surface states and a shallow energy distribution than TiO2 nanoparticles under the same film thickness. Furthermore, the fitted data indicate that the electron transport in TiO2 submicrospheres film was faster than in traditional nanoparticles film owing to their high electron concentration and shallow surface states energy distribution. The discussion highlights the location of surface states in the band gap region of TiO2 film, which plays an important role in electron transport and charge recombination in DSSCs.